2010
DOI: 10.1007/s10342-010-0462-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of somatic embryogenesis and analysis of genetic fidelity of in vitro-derived plantlets of Bambusa nutans Wall., using AFLP markers

Abstract: Bambusa nutans Wall., is an evergreen, perennial, and multipurpose bamboo having strong culms, which are largely used for construction, scaffolding, craft purposes, pulp, and paper industry. Multiple shoots from nodal segments (3-4 cm) of young branches of mature culms were established in Murashige and Skoog (1962) (MS) medium supplemented with various concentrations of 6-benzylaminopurine (BAP) (1.0-6.0 mg l -1 ) or in combination with a-naphthaleneacetic acid (NAA) (0.5-1.0 mg l -1 ) or kinetin (Kn) (1.0-2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Since shoot organogenesis was achieved through intermediate callus phase, therefore, clonal fidelity using regenerated shoots was tested using RAPD and ISSR markers. The utility of molecular markers in studying clonal fidelity of in vitro propagated plants is well documented (Khatab and El-Banna 2011, Kumar et al 2010, Rani and Raina 2000, Nag et al 2012, Mehta et al 2011). All the scored markers (both by RAPD and ISSR) were found to be monomorphic indicating the genetic uniformity of regenerated plants ( Figure 1C-D).…”
Section: Discussionmentioning
confidence: 99%
“…Since shoot organogenesis was achieved through intermediate callus phase, therefore, clonal fidelity using regenerated shoots was tested using RAPD and ISSR markers. The utility of molecular markers in studying clonal fidelity of in vitro propagated plants is well documented (Khatab and El-Banna 2011, Kumar et al 2010, Rani and Raina 2000, Nag et al 2012, Mehta et al 2011). All the scored markers (both by RAPD and ISSR) were found to be monomorphic indicating the genetic uniformity of regenerated plants ( Figure 1C-D).…”
Section: Discussionmentioning
confidence: 99%
“…The values of genetic instability in this study (≤ 10 %) correspond to absent to low levels of variation reported for SE (0 -10 %) as in Cassia occidentalis, Ipomoea batatas, Picea abies, Distylium chinense, Quercus robur, Psidium guajava, Olea maderensis, O. europea, etc. (Fourré et al 1997, Lopes et al 2006, Valladares et al 2006, Triqui et al 2008, Yang et al 2008, Mehta et al 2011, Rai et al 2012, Bobadilla et al 2013, Li et al 2014, Carra et al 2016, Morais-Lino et al 2016, Naz et al 2016, Vinoth and Ravindhran 2016. It is possible that the explants selected may be less susceptible to genetic instability (DeVerno et al 1999) and, as a consequence, the results differ from those reported by others using the same morphogenetic route with intermediate levels of variation (17 -31 %) (Müller et al 1990, López et al 2004, Wilhelm et al 2005, Burg et al 2007, Prado et al 2010, Dey et al 2015.…”
Section: Resultsmentioning
confidence: 98%
“…SE in M. dealbata may reduce the genetic uniformity of the regenerants through the callus phase presented both during primary and secondary SE (Sharma et al 2007, Rai et al 2012. The culture environment might also present stresses leading to a loss of programmed cellular control (Mehta et al 2011). In Pinus pinaster and Quercus robur, prolonged propagation reduced genetic stability (Endemann et al 2001, Marum et al 2009.…”
Section: Resultsmentioning
confidence: 99%
“…1% Bavistin is reported as most widely used concentration as surface sterilants during in vitro propagation of bamboo. Though there are exceptions also, Bavistin reported @ 0.1% in Bambusa nutans Wall 68 ; 0.5% in B.nutans 80 ; 0.2% in D. strictus 81 . Besides Bavistin, other fungicides that are reported till date as surface sterilants for in vitro propagation of bamboo are Benomyl and Mancozeb.…”
Section: Surface Sterilants For Bamboo Tissue Culturementioning
confidence: 98%
“…Explant collected at rainy season is having higher bud breaking coupled with high chances of contamination. More than 60% endogenous contamination during rainy season reported in B. nutans 68 . Collection of nodal explants (Arundinaria callosa Munro) during rainy season showed 30% more contaminations than that of after monsoon season 69 .…”
Section: Edaphic Factors Vis-à-vis Contaminationmentioning
confidence: 99%